USING VIDEO MATERIALS IN TEACHING ENGLISH - Nazarov, Rustam (Журнал иностранных языков и лингвистики, 2023)
The article deals with some aspect of using video in teaching English as a foreign language. Using video in teaching a foreign language opens up ample opportunities for the teacher and students in mastering the language and foreign culture. Visual information allows you to better understand and consolidate factual information and language features of speech, as visual support contributes to a complete and accurate understanding of the meaning, activating attention and memory and contributing to the development and skills of listening and speaking